The Church and the State : the imperative of collaborating towards political stability in Nigeria - Onaiyekan, John O. (Abuja, Nigeria: Gaudium et Spes Institute, 2008)
The six part work has as general focus, Archbishop Onaiyekan's recurrent plea that the church and state should endeavour to collaborate towards the realization of political tability and economic development in Nigeria.
osc 18/09/13
Loans
Keywords: Archbishop John Onaiyekan; Political Thought; church and state